The Amish marriage arrangement - Johns, Patricia, (Romance writer) (Sydney, NSW : Harlequin Mills & Boon, 2023)
Forgiving past mistakes could open up a whole new future .. After leaving the community years ago, Amish bad boy Arden Stoltzfus is back to convince his grandfather to move to Ohio. But neighbour Sarai Peachy stands in his way - her grandmother is sweet on the older gentleman. When a sudden windstorm damages her grandmother's home, Sarai and Arden are forced to work together on the repairs. Will spending time with the former heartbreaker prove to her Arden is a changed man?
Title from title screen.
General.
Mode of access : Available online.
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Electronic books; Romance fiction